Sexo-- que es? : desarrollo, cambios corporales, sexo y salud sexual - Harris, Robie H.; Emberley, Michael; Saslavsky, Irene (Barcelona, Spain : Serres, 2005)
Contains information on how your body changes as you grow up and information on sexuality.
English title: It's perfectly normal.
Includes index.
5-A.
10-A.
940
Reading Lexile
Keywords: Sex instruction for children -- Juvenile literature; Hygiene, Sexual -- Juvenile literature